Comparative Genomics Reveals Accelerated Evolution of Fright Reaction Genes in Ostariophysan Fishes - Yang, Liandong; Jiang, Haifeng; Chen, Juan; Lei, Yi; Sun, Ning; Lv, Wenqi; Near, Thomas J.; He, Shunping (Frontiers in Genetics, 2019)
The ostariophysian fishes are the most species-rich clade in freshwaters. This diversification has been suggested to be associated with the fright reaction presented in most ostariophysians. However, the genetic forces that underlie fright reaction remains poorly understood. In the present study, through integrating behavioural, physiological, transcriptomic, and evolutionary genomic analyses, we found that the fright reaction has a broad impact on zebrafish at multiple levels, including changes in swimming behaviors, cortisol levels, and gene expression patterns. In total, 1555 and 1599 differentially expressed genes were identified in olfactory mucosae and brain of zebrafish, respectively, with a greater number upregulated after the fright reaction. Functional annotation showed that response to stress and signal transduction were strongly represented, which is directly associated with the fright reaction. These differentially expressed genes were shown to be evolved accelerated under the influence of positive selection, indicating that protein-coding evolution has played a major role in fright reaction. We found the basal vomeronasal type 2 receptors (v2r) gene, v2rl1, displayed significantly decrease expression after fright reaction, which suggests that v2rs may be important to detect the alarm substance and induce the fright reaction. Collectively, based on our transcriptome and evolutionary genomics analyses, we suggest that transcriptional plasticity of gene may play an important role in fright reaction in ostariophysian fishes.